Evaluation of the Career Development Program for Educational Personnel in Ganesha University of Education in Order to Improve University Performance - RISADIANTA, Gede Dwi; WIDIASTINI, Ni Made Ary; RAHMAWATIIS, Putu Indah (Journal of Tourism Economics and Policy, 2025)
Ganesha University of Education (Undiksha) is one of the tertiary institutions that demands superior skills, increased productivity and knowledge related to employee performance with the aim of encouraging university performance achievements. This demand emphasizes the need for career development for educational staff at Undiksha. Therefore, it is necessary to evaluate the implementation of educational staff career development programs to improve university performance. This study aims to identify and evaluate the effectiveness of implementing the career development program for Undiksha education staff. This research was conducted using a qualitative descriptive method. The results of this study indicate that Undiksha has various career development programs for education staff through the provision of training, workshops, comparative studies, as well as through educational assistance to increase the education level (S-2 and S-3) of education staff. Based on the evaluation carried out on the career development program for educational staff, the programs implemented by Undiksha were able to improve the university's overall performance. The results of this research are expected to contribute both theoretically and practically related to the importance of career development for educational staff in tertiary institutions in order to improve university performance.